Openness to experience, a personality trait that reduces susceptibility to memory age-based stereotype threat - Bouazzaoui, Badiâa; Fay, Séverine; Alibran, Emilie; Martinez, Léa; Pinard, Florent; Kerhardy, Nolwenn; Onsekiz, Tugba; Taconnat, Laurence (Frontiers in Psychology, 2024)
Introduction Age-based stereotype threat (ABST), the concern of being judged according to a negative age stereotype may lead to underperformance in the stereotype domain. The present study aims to replicate the negative effect of ABST on episodic memory. Importantly, we further examine openness to experience as a potential buffer of the ABST effect as well as the role that different memory strategies may play in episodic memory performance. Method Seventy-five older adults were randomly assigned to the ABST condition or the control condition before taking a word-stem cued recall memory task. They learned word-lists with either a repetition strategy, low resource demanding but less efficient, or a mental imagery strategy, high resource demanding but more efficient. Openness was measured with the Big-5 personality questionnaire. Results ABST reduced memory performance and disrupted more the recall of words learned with the imagery strategy. The results also showed that openness predicted recall performance associated with the imagery strategy only in the threatened group. Conclusion These results indicated that a high level in openness may disrupt the negative effect of ABST by improving the capacity of threatened people to execute efficient, resource demanding memory strategies. This finding supports the idea that contextual factors as well as individual characteristics such as personality, need to be considered when assessing episodic memory in aging.